Antibiotic Resistance Genes of Class 1 Integrons in Chicken Microbiomes Modulated by Prebiotics - Almutrafy, Abeer (2021)
Class 1 integrons are genetic elements of bacteria that contribute to the abundance of antibiotic resistance. Poultry products are thought to be one of the most important reservoirs for transmission of antimicrobial resistance bacteria (AMR) via foodborne zoonotic pathogens reducing the effectiveness of antimicrobial treatments. Prebiotics have attracted attention as an aid to reduce pathogen loads and support the intestinal health of poultry. However, whether prebiotics directly reduce the expansion of bacterial populations carrying antibiotic resistance genes (ARG) or reduce their transmission from livestock, is not known. This thesis investigates the potential role of prebiotic galactooligosaccharides (GOS) in the mitigation of ARG prevalence in the microbiomes of broiler chickens reared under biosecure or commercial conditions.